A palaeomagnetic and 40Ar/39Ar study of mafic dykes in southern Sweden: A new Early Neoproterozoic key-pole for the Baltic Shield and implications for Sveconorwegian and Grenville loops - Elming, S.; Pisarevsky, Sergei; Layer, P.; Bylund, G. (Elsevier BV, 2014)
We present the results of palaeomagnetic and40Ar/39Ar studies of the Proterozoic mafic dykes in the Norrköping and Falun areas of the southern Sweden. The primary remanence of two 939 ± 3 Ma dykes is supported by the rigorous baked contact test. The remanence direction of two other dykes, one of which was previously U–Pb dated at 946 ± 1 Ma is close to the reverse direction of 939 Ma dykes. Using these results together with previously published 935 ± 5 Ma palaeomagnetic data from the Göteborg-Slussen mafic dykes and some dykes from the Falun area we calculated the mean 946–935 Ma palaeopole for Baltica (0.9° S, 240.7° E, A95= 6.7), which can be qualified as the key pole. Using this pole together with other date we conclude that the Grenville and Sveconorwegian loops of Laurentian and Baltican Apparent Polar Wander Paths are temporary displaced by 100–150 m.y. We propose new palaeogeographic reconstructions of Baltica and Laurentia at ca. 940 Ma and ca. 850 Ma. We also present two new Mesoproterozoic non-key poles from 1410 Ma and 1595 Ma dykes.